2023
DOI: 10.3390/ijms24065978
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Composition and Its Metabolites Are a Key Regulating Factor for Malignant Transformation, Metastasis and Antitumor Immunity

Abstract: The genetic and metabolomic abundance of the microbiome exemplifies that the microbiome comprises a more extensive set of genes than the entire human genome, which justifies the numerous metabolic and immunological interactions between the gut microbiota, macroorganisms and immune processes. These interactions have local and systemic impacts that can influence the pathological process of carcinogenesis. The latter can be promoted, enhanced or inhibited by the interactions between the microbiota and the host. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 132 publications
1
6
0
Order By: Relevance
“…As next step of this study, because microbiome-derived metabolites act both as nutrients and as messenger molecules to the host, we focused on the alterations of metabolic functions in the resident microbiome to elucidate how lung cancer modulation of the lung and gut microbiota affected their metabolic functions during lung cancer progression [ 7 , 9 , 11 ]. Consequently, “retinol metabolism” in the lung microbiome was significantly activated in mice with lung cancer, whereas the metabolic function in the gut microbiome was significantly attenuated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As next step of this study, because microbiome-derived metabolites act both as nutrients and as messenger molecules to the host, we focused on the alterations of metabolic functions in the resident microbiome to elucidate how lung cancer modulation of the lung and gut microbiota affected their metabolic functions during lung cancer progression [ 7 , 9 , 11 ]. Consequently, “retinol metabolism” in the lung microbiome was significantly activated in mice with lung cancer, whereas the metabolic function in the gut microbiome was significantly attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested that patients with colon cancer have different gut microbiome compositions compared to healthy volunteers, and some bacteria that comprise the human gut microbiome can be partially linked to the development of colon cancer [ 6 ] through the alteration of their immune and metabolic functions [ [7] , [8] , [9] , [10] ]. Additionally, a previous clinical study revealed that the lower airway dysbiotic signature was more prevalent in a stage IIIB–IV tumor–node–metastasis lung cancer group and was associated with poor prognosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between the gut flora and the host immune-metabolic system are complex, and can have local and systemic effects on the host ( Lozenov et al, 2023 ; Riazati et al, 2023 ). Clinical studies or experimental animal studies have demonstrated a relationship between gut microbial composition and disease, and found that dysbiosis appears to be a precursor to carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing a patient's gut microbiota, medical professionals may be able to predict the patient's response to certain drugs [ 175 ]. Moreover, in CRC, numerous strategies have been demonstrated to target and alter the composition of the gut microbiota, considering both microbial physiology and/or their metabolites that directly or indirectly lead to CRC [ 176 ]. These strategies include dietary interventions, antibiotic treatments, probiotics, prebiotics, and postbiotics, as well as FMT [ 177 ] ( Fig.…”
Section: Targeting the Gut Microbiome In Gi Cancer Therapymentioning
confidence: 99%